Edible bio-nano-hybrid coatings for food protection based on pectins and LDH-salicylate: Preparation and analysis of physical properties. (June 2016) - Gorrasi, Giuliana; Bugatti, Valeria
Abstract: Novel active coatings from renewable sources were developed using a pectin matrix and a modified layered double hydroxyde (LDH), as filler. The active molecule, ionically bonded to the LDH, was sodium salicylate. The hybrid filler loading was 5 wt% of LDH-salicylate, with a total content of active molecule into the composites of 1.6 wt%. The degree of plasticization of the composites varied in the range 4–16 vol % of glycerol. Morphological, thermal and barrier properties of the composites were analyzed. The x-ray analysis showed a complete delamination of the hybrid filler at any glycerol loading. The thermal degradation behavior and mechanical properties resulted strictly influenced by the glycerol content. Barrier properties (sorption, diffusion and permeability) to water vapor indicated that composite plasticized with 4 vol% of glycerol showed the best improvement of barrier properties. This suggested that the interaction pectin-active filler-degree of glycerol plays a significant role in determining the transport phenomena. Fresh apricots were coated with the active composite plasticized with 4 vol % of glycerol, demonstrating the efficiency of this formulation in extending the preservation of such fruits. Highlights: Edible active coatings based on pectins filled with LDH-salicylate were prepared. Glycerol, as plasticizer, was added in the range 4–16 vol%. Thermal, mechanical and barrier properties of the composites were evaluated. Fresh apricots were coated with the active composite at 4 vol% of glycerol. This chosen formulation extended the preservation time of such fruits.